Experiment Research and Design of a New Wet Type Mechanical Joint Brake System Applied to Long Stroke - Yin Xiaoqing (Jixie chuandong)
In order to solve the problems of long stroke mechanical joint brake system difficulty in design,manufacturing and repair costs are high,a new wet brake in long stroke mechanical joint brake system is introduced,and the expressions of key design index of new braking system is derived,finally,the experiment platform for the research of the variation law of braking characteristics of a new wet type long stroke mechanical joint brake system is built. The results show that the new joint brake in the initial stage of braking has certain drag torque phenomenon in single braking condition. The new joint brake increased significantly at the initial stage of braking torque in continuous braking condition,with the increase of number of brake,brake torque variation tends to be stable. When the braking times of the number of 0 600 times,the brake temperature increased rapidly,when the braking times reach 1200,the brake temperature reaches thermal equilibrium. The new wet type mechanical joint brake system torque fluctuation in two kinds of braking conditions rate all meet the design requirements,the design scheme is feasible.